Innovation Constraints in Traditional Firms in Emerging Markets: A Qualitative Analysis - Estuti Fitri Hartini; Anaiza Azlia; Lusiana Ratna Primata (International Journal of Business, Economics & Financial Studies, 2025)
Innovation plays a crucial role in sustaining competitiveness within traditional-based industries, particularly in sectors undergoing technological and market transformation. However, many traditional firms still face structural and strategic challenges in developing sustainable innovation capabilities. This study aims to analyze the constraints on innovation experienced by PT. X, an Indonesian herbal medicine and pharmaceutical company, aims to identify strategic implications for improving its long-term innovation performance. The research adopts a qualitative, descriptive–exploratory design using secondary data sources, including corporate documents and relevant scientific literature. Data were analyzed using thematic analysis in NVIVO to systematically identify patterns and relationships among key innovation issues. The analysis revealed four main themes influencing the company’s innovation performance: weaknesses in product innovation, limitations in diversification and business structure, efficiency and financial constraints, and dependence on external factors such as natural raw materials and limited international market expansion. The findings indicate that the company’s innovation strategy remains largely focused on incremental product improvements, while limited business diversification and suboptimal resource utilization limit opportunities for research-driven innovation and technological development. In addition, dependence on agricultural raw materials and domestic market conditions further complicates the innovation process. The study concludes that innovation challenges within traditional-based firms are multidimensional and require an integrated strategic approach that strengthens research and development, improves operational efficiency, diversifies business portfolios, and enhances supply chain and international market strategies. These findings contribute to understanding innovation dynamics in traditional industries and provide practical insights for developing sustainable innovation strategies in emerging markets.